IMPLEMENTATION OF DIGITAL TECHNOLOGIES IN THE LESSONS OF INDUSTRIAL TRAINING IN THE PROFESSION OF ‘INSTRUMENTATION AND AUTOMATION MECHANIC’ (Innovative professional education, 2025)
The article defines the role of today’s master of vocational training. The main methods of organizing students’ cognitive activity are described. It is indicated that visual and practical methods of conveying information are the most effective. The article determines the necessity and expediency of implementing digital technologies in industrial training lessons for «Instrumentation and Automation Control Mechanics»
Keywords: digital technologies, vocational education, methods, instrumentation and measurement devices, test systems development